In-Vitro anti-inflammatory activity of S. xanthocarpum and A. officinarum herb by Human red blood cell membrane stabilization method - journal, Chandra Shekhar Singh; Gupta, Shailesh; jain, Alok Pal (Journal of Drug Delivery and Therapeutics, 2019)
Natural remedies are more acceptable in the belief that they are safer with fewer side effects than the synthetic ones. Herbal formulations have growing demand in the world market. Solanum xanthocarpum herb is highly used by the rural and tribal people in curing various disorders. The aim of the current investigation is evaluation of anti inflammatory activity of solanum xanthocarpum extract and Alpinia officinarum. In-vitro anti-inflammatory study performed by percentage inhibition of Human red blood cell (HRBC) membrane stabilization method. Four different concentration of extract 1mg/ml, 2 mg/ml, 4 mg/ml and 6 mg/ml were used for each extract. Among which ethanolic extract of S. xanthocarpum at concentration 6 mg/ml showed 50.1 % protection of HRBC in hypotonic solution and A. officinarum extract at concentration 6 mg/ml showed 56.89 while combination of extract (1:1 ratio) at concentration 6 mg/ml showed 67.89 % protection of HRBC in hypotonic solution. All the results were compared with standard indomethacin which showed 70.0 % protection at concentration 2.5 mg/ml Keyword: Natural remedies, anti-inflammatory, Human red blood cell (HRBC) membrane stabilization, hypotonic solution.